2014
DOI: 10.3390/en7031770
|View full text |Cite
|
Sign up to set email alerts
|

Localized Climate and Surface Energy Flux Alterations across an Urban Gradient in the Central U.S.

Abstract: Long-term urban and rural climate data spanning January 1995 through October 2013 were analyzed to investigate the Urban Heat Island (UHI) effect in a representative mid-sized city of the central US. Locally distributed climate data were also collected at nested low density urban, recently developed, and high density urban monitoring sites from June through September 2013 to improve mechanistic understanding of spatial variability of the UHI effect based upon urban land use intensity. Long-term analyses (1995)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 27 publications
5
27
0
Order By: Relevance
“…The results from the one-way ANOVA tests showed no significant differences (p > 0.05) in the seven-year average precipitation between sites in agreement with a recent publication by Hubbart et al [33]. Hubbart et al [33] showed that the differences in precipitation between urban and rural sites were not significant at the 95% confidence level in the HCW.…”
Section: Map Modelingsupporting
confidence: 79%
See 2 more Smart Citations
“…The results from the one-way ANOVA tests showed no significant differences (p > 0.05) in the seven-year average precipitation between sites in agreement with a recent publication by Hubbart et al [33]. Hubbart et al [33] showed that the differences in precipitation between urban and rural sites were not significant at the 95% confidence level in the HCW.…”
Section: Map Modelingsupporting
confidence: 79%
“…Hubbart et al [33] showed that the differences in precipitation between urban and rural sites were not significant at the 95% confidence level in the HCW. However, precipitation was shown to be slightly greater by 3.3% in the urban area of the watershed indicating a slight influence of urban land use on total annual precipitation in the rapidly urbanizing lower elevations of HCW [38].…”
Section: Map Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the fact that forest ecosystems (biomass and soils) are highly productive in terms of carbon sequestration processes [3,68,69]. In addition, planting trees has long been used as a strategy to mitigate urban heat island effects [70] by multiple mechanisms, including decreased albedo [71].…”
Section: Discussionmentioning
confidence: 99%
“…Land use/land cover change (e.g., forest removal, agricultural conversion, urbanization) has repeatedly and conclusively been shown to alter rates of mass (e.g., sedimentation of waterways, increased nutrient loadings) and energy flux (e.g., urban heat island, water temperature regime change) [1][2][3][4]. Such alterations impact water quality (e.g., chemical composition, pathogen presence and persistence) and quantity regimes (e.g., low flows, peak flows, flooding) [5][6][7][8], and can ultimately result in ecosystem degradation.…”
Section: Introductionmentioning
confidence: 99%